Psychological Outcomes of BPE Student: A Comparative Study - Kate Mylicka C. Boucher (American Journal of Physical Education and Health Science, 2026)
College students' psychological outcomes are primary global concern today. This study examined the psychological outcomes of BPE students in Davao City, comparing them by age, sex, and year level. The study used a quantitative, descriptive-comparative design with a structured survey administered to 100 randomly selected BPE students. Statistical analyses using ANOVA and t-test showed no significant differences in psychological outcomes by age, sex, or year level. Overall, respondents exhibited a moderate level of psychological outcomes. The results highlight the need to explore factors like teaching methods, support systems, and interventions to improve BPE students psychological outcomes.